FEATURES AND PROBLEMS OF PROFESSIONAL VOCAL EDUCATION AND REFORM EXPLORATION IN MODERN CHINA - Chen Xi, (International Journal of Innovative Technologies in Social Science, 2024)
Vocal music teaching occupies an important place in the music education and teaching system of colleges and universities, and is also one of the core professional courses for music teaching in colleges and universities. Although vocal music teaching in colleges and universities in China has achieved good results, with the development of society, the traditional teaching model in the PRC has been unable to meet the needs of modern development teaching, especially in terms of concept as well as teaching content and method, which is serious hinders the development of modern teaching. Therefore, it is necessary to reform vocal teaching in Chinese universities. This article first briefly analyzes the current situation of vocal teaching in colleges and universities, and then suggests some strategies for reforming teaching that should be aimed at developing professional talents. The author talks about the need to reform modern teaching methods to diversify teaching and offer students flexible and targeted learning based on real situations and personal characteristics of students to meet the needs of social talent development.